2015
DOI: 10.1007/s11104-015-2563-9
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating the impact of root orientation on root quantification using ground-penetrating radar

Abstract: Background and aims Ground-penetrating radar (GPR) has provided a non-invasive means for field root investigation. However, the horizontal cross angle (x) of root orientation intersecting a survey line considerably impacts the amplitude area (A) reflected from a root and impairs the accuracy of GPR-based root quantification. Prediction of A(90°) (the value of A scanning at x=90°) from multiple A(x) measurements could correct such impact. Previous method of A(90°) prediction focused on target roots at field poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…As a linear target, the reflection amplitude of root is influenced by the root direction relative to the antenna [38,39]. Tanikawa [40] and Guo [32] analyzed the impact of horizontal azimuth angle on root detection using GPR and pointed out that horizontal orientation significantly influences both the amplitude and the opening angle of reflected hyperbolic signals, which supports our results (Figure 5c). However, few studies have focused on the combined effects of both horizontal and vertical inclination of roots in GPR detection.…”
Section: Root Distribution Factorssupporting
confidence: 86%
See 1 more Smart Citation
“…As a linear target, the reflection amplitude of root is influenced by the root direction relative to the antenna [38,39]. Tanikawa [40] and Guo [32] analyzed the impact of horizontal azimuth angle on root detection using GPR and pointed out that horizontal orientation significantly influences both the amplitude and the opening angle of reflected hyperbolic signals, which supports our results (Figure 5c). However, few studies have focused on the combined effects of both horizontal and vertical inclination of roots in GPR detection.…”
Section: Root Distribution Factorssupporting
confidence: 86%
“…Trench I-III were originally designed for the study of root orientation by Guo et al [32], with 4 m length and 0.5 m depth. Figure 1a shows trench I as an example.…”
Section: Controlled Experimentsmentioning
confidence: 99%
“…Soil temperature and the amount of nonliving organic material also are known to influence GPR signal; therefore, extensive calibration must be undertaken, especially for nonuniform soils. Even in ideal conditions (relatively dry, sandy soils), careful comparisons with excavated root systems have not shown strong correlations, especially for roots growing downward (Zenone et al, 2008;Guo et al, 2015a). To date, GPR has not been shown to be capable of detecting fine (approximately less than 2 mm) roots, which may constitute the majority of root length for many plants (Pierret et al, 2005;Brown et al, 2009).…”
Section: Plant Root Phenotypingmentioning
confidence: 99%
“…However, these studies have only utilized either single direction scanning transects [7,[19][20][21][25][26][27]29,30,42,44,45] or perpendicular, two-direction scanning transects [28,41,43]. It has been shown that the angle at which the GPR antenna crosses over a root affects the amplitude of the reflected waveform, thus affecting the estimated size of the root [46][47][48]. Guo et al [48] examined a three-direction method to correct for non-perpendicular root orientation relative to the GPR transects, but did not extrapolate their data to system level biomass estimation.…”
Section: Transect Configurationmentioning
confidence: 99%
“…It has been shown that the angle at which the GPR antenna crosses over a root affects the amplitude of the reflected waveform, thus affecting the estimated size of the root [46][47][48]. Guo et al [48] examined a three-direction method to correct for non-perpendicular root orientation relative to the GPR transects, but did not extrapolate their data to system level biomass estimation. No research has been conducted to determine if models built using four scan directions have a higher potential to reduce variability based on root orientation compared to models based on fewer transect directions.…”
Section: Transect Configurationmentioning
confidence: 99%